2023
DOI: 10.1109/access.2022.3232287
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Detection in Banking Data by Machine Learning Techniques

Abstract: As technology advanced and e-commerce services expanded, credit cards became one of the most popular payment methods, resulting in an increase in the volume of banking transactions. Furthermore, the significant increase in fraud requires high banking transaction costs. As a result, detecting fraudulent activities has become a fascinating topic. In this study, we consider the use of class weighttuning hyperparameters to control the weight of fraudulent and legitimate transactions. We use Bayesian optimization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…- The proliferation of credit card usage in e-commerce has led to an increase in fraudulent activities, resulting in the need for effective fraud detection methods, as discussed in [5]. This study introduces weight-tuning hyperparameters, Bayesian optimization, and ensemble learning techniques to enhance fraud detection using machine learning models such as CatBoost, LightGBM, XGBoost, and deep learning.…”
Section: Detailed Study Of Fraud Detection Methodsmentioning
confidence: 99%
“…- The proliferation of credit card usage in e-commerce has led to an increase in fraudulent activities, resulting in the need for effective fraud detection methods, as discussed in [5]. This study introduces weight-tuning hyperparameters, Bayesian optimization, and ensemble learning techniques to enhance fraud detection using machine learning models such as CatBoost, LightGBM, XGBoost, and deep learning.…”
Section: Detailed Study Of Fraud Detection Methodsmentioning
confidence: 99%
“…The model is put up against other classi ers like NB, SVM, and ANN and is discovered to offer effective results with high accuracy. The study [24][25][26] suggests using Bayesian optimization and class weight-tuning to identify fraudulent features in credit card transactions using gradient boosting and category boosting as an ensemble approach, the authors found Bayesian optimization to be e cient in improving computational time and performance. Additionally, deep learning [24] is used to optimize the hyperparameters and get better outcomes.…”
Section: Machine Learning Algorithms For Fraud Detectionmentioning
confidence: 99%
“…Then, if anomalous behavior or suspicious transactions are detected, the system activates an alert. To review and verify the transactions, the bank or customer can receive this alert as a text message or notification (11)(12)(13)(14)(15).…”
Section: Literature Reviewmentioning
confidence: 99%
“…11,776 transactions is entered as input to the LightGBM algorithm, and again the supervised learning steps are performed on the training data of the filtered dataset, and then data testing is performed on all 11,776 transactions, and finally the results are according to the matrix The confusion of Figure4is obtained.…”
mentioning
confidence: 99%